KKN UNP 2025: Dalam Proyek Ecobrick di Dalko Koto Panjang - Rido Putra; Vara Citra Ananda; Indah Surya Hasari; Lala Deswita; Alya Fitriani; Qadrian Zakhri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Plastic waste scattered in the environment is a serious problem for life because of the many negative impacts caused by the substances contained in it. Plastic waste takes decades or even hundreds of years to decompose. One creative and innovative way to reduce the problem of plastic waste is by utilizing it in the manufacture of various functional products with the ecobrick method. This article discusses how to make ecobricks into environmentally friendly writing creations in the Dalko Jorong Koto Panjang sub-district. This project activity includes the active participation of students and the Jorong Koto Panjang community in the process of collecting plastic waste, making ecobricks, and assembling iron that says "AIE UBEK" which is one of the well-known bathing places in Jorong Koto Panjang. The results of the activity show a positive impact in addition to providing aesthetic value, but also increasing awareness for students and the community about the importance of protecting the environment from the threat of plastic waste.